Investigation on some matrix‐dominated properties of hybrid multiscale composites based on carbon fiber/carbon nanotube modified epoxy. Issue 2 (27th June 2012) - Wang, Baichen; Zhou, Xia; Yin, Junshan; Wang, Li
Abstract Continuous fiber reinforced polymer‐based composites have outstanding fiber‐dominated properties but unsatisfactory matrix‐dominated performances. In this investigation, carbon fiber reinforced epoxy composites modified with carbon nanotubes (CNTs) were fabricated to evaluate the effects of CNTs on some matrix‐dominated properties of the resulting hybrid multiscale composites. Carboxylic acid functionalized multiwalled CNTs were dispersed in epoxy by using high energy sonication, followed by the fabrication of the composites laminates with the epoxy/CNTs dispersion. The dispersion quality of CNTs in epoxy and the capillary infiltration of continuous fiber with the epoxy/CNTs dispersion were characterized using optical microscope and capillary experiment to optimize the processing parameters. A CNTs loading of 1 wt % significantly improved the flexural strength and interlaminar shear strength of the composites containing varying scale reinforcements by 51.8% and 34.2%, respectively, as compared to the control carbon/epoxy composites. Scanning electron microscopy was used to examine the fracture surface of the failed specimens. The moisture absorption behavior of the carbon fiber/epoxy composites with and without CNTs was investigated by comparing the weight gain and shear properties degradation in distilled water and 1.5 wt % brine. The integration of CNTs in composites is found to contribute to the medium‐dependent moisture adsorption behavior. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013